The Stacks project

\begin{equation*} \DeclareMathOperator\Coim{Coim} \DeclareMathOperator\Coker{Coker} \DeclareMathOperator\Ext{Ext} \DeclareMathOperator\Hom{Hom} \DeclareMathOperator\Im{Im} \DeclareMathOperator\Ker{Ker} \DeclareMathOperator\Mor{Mor} \DeclareMathOperator\Ob{Ob} \DeclareMathOperator\Sh{Sh} \DeclareMathOperator\SheafExt{\mathcal{E}\mathit{xt}} \DeclareMathOperator\SheafHom{\mathcal{H}\mathit{om}} \DeclareMathOperator\Spec{Spec} \newcommand\colim{\mathop{\mathrm{colim}}\nolimits} \newcommand\lim{\mathop{\mathrm{lim}}\nolimits} \newcommand\Qcoh{\mathit{Qcoh}} \newcommand\Sch{\mathit{Sch}} \newcommand\QCohstack{\mathcal{QC}\!\mathit{oh}} \newcommand\Cohstack{\mathcal{C}\!\mathit{oh}} \newcommand\Spacesstack{\mathcal{S}\!\mathit{paces}} \newcommand\Quotfunctor{\mathrm{Quot}} \newcommand\Hilbfunctor{\mathrm{Hilb}} \newcommand\Curvesstack{\mathcal{C}\!\mathit{urves}} \newcommand\Polarizedstack{\mathcal{P}\!\mathit{olarized}} \newcommand\Complexesstack{\mathcal{C}\!\mathit{omplexes}} \newcommand\Pic{\mathop{\mathrm{Pic}}\nolimits} \newcommand\Picardstack{\mathcal{P}\!\mathit{ic}} \newcommand\Picardfunctor{\mathrm{Pic}} \newcommand\Deformationcategory{\mathcal{D}\!\mathit{ef}} \end{equation*}

14.23 Simplicial objects and chain complexes

Let $\mathcal{A}$ be an abelian category. See Homology, Section 12.12 for conventions and notation regarding chain complexes. Let $U$ be a simplicial object of $\mathcal{A}$. The associated chain complex $s(U)$ of $U$, sometimes called the Moore complex, is the chain complex

\[ \ldots \to U_2 \to U_1 \to U_0 \to 0 \to 0 \to \ldots \]

with boundary maps $d_ n : U_ n \to U_{n - 1}$ given by the formula

\[ d_ n = \sum \nolimits _{i = 0}^ n (-1)^ i d^ n_ i. \]

This is a complex because, by the relations listed in Remark 14.3.3, we have

\begin{eqnarray*} d_ n \circ d_{n + 1} & = & (\sum \nolimits _{i = 0}^ n (-1)^ i d^ n_ i) \circ (\sum \nolimits _{j = 0}^{n + 1} (-1)^ j d^{n + 1}_ j) \\ & = & \sum \nolimits _{0 \leq i < j \leq n + 1} (-1)^{i + j} d^ n_{j - 1} \circ d^{n + 1}_ i + \sum \nolimits _{n \geq i \geq j \geq 0} (-1)^{i + j} d^ n_ i \circ d^{n + 1}_ j \\ & = & 0. \end{eqnarray*}

The signs cancel! We denote the associated chain complex $s(U)$. Clearly, the construction is functorial and hence defines a functor

\[ s : \text{Simp}(\mathcal{A}) \longrightarrow \text{Ch}_{\geq 0}(\mathcal{A}). \]

Thus we have the confusing but correct formula $s(U)_ n = U_ n$.

Proof. Clear from Lemma 14.22.1. $\square$

Lemma 14.23.2. Let $\mathcal{A}$ be an abelian category. Let $A$ be an object of $\mathcal{A}$ and let $k$ be an integer. Let $E$ be the object described in Lemma 14.22.4. Then the complex $s(E)$ is acyclic.

Proof. For a morphism $\alpha : [n] \to [k + 1]$ we define $\alpha ' : [n + 1] \to [k + 1]$ to be the map such that $\alpha '|_{[n]} = \alpha $ and $\alpha '(n + 1) = k + 1$. Note that if the image of $\alpha $ is $[k]$ or $[k + 1]$, then the image of $\alpha '$ is $[k + 1]$. Consider the family of maps $h_ n : E_ n \to E_{n + 1}$ which maps the summand corresponding to $\alpha $ to the summand corresponding to $\alpha '$ via the identity on $A$. Let us compute $d_{n + 1} \circ h_ n - h_{n - 1} \circ d_ n$. We will first do this in case the category $\mathcal{A}$ is the category of abelian groups. Let us use the notation $x_\alpha $ to indicate the element $x \in A$ in the summand of $E_ n$ corresponding to the map $\alpha $ occurring in the index set. Let us also adopt the convention that $x_\alpha $ designates the zero element of $E_ n$ whenever $\mathop{\mathrm{Im}}(\alpha )$ is not $[k]$ or $[k + 1]$. With these conventions we see that

\[ d_{n + 1}(h_ n(x_\alpha )) = \sum \nolimits _{i = 0}^{n + 1} (-1)^ i x_{\alpha ' \circ \delta ^{n + 1}_ i} \]

and

\[ h_{n - 1}(d_ n(x_\alpha )) = \sum \nolimits _{i = 0}^ n (-1)^ i x_{(\alpha \circ \delta _ i^ n)'} \]

It is easy to see that $\alpha ' \circ \delta ^{n + 1}_ i = (\alpha \circ \delta _ i^ n)'$ for $i = 0, \ldots , n$. It is also easy to see that $\alpha ' \circ \delta ^{n + 1}_{n + 1} = \alpha $. Thus we see that

\[ (d_{n + 1} \circ h_ n - h_{n - 1} \circ d_ n)(x_\alpha ) = (-1)^{n + 1} x_\alpha \]

These identities continue to hold if $\mathcal{A}$ is any abelian category because they hold in the simplicial abelian group $[n] \mapsto \mathop{\mathrm{Hom}}\nolimits (A, E_ n)$; details left to the reader. We conclude that the identity map on $E$ is homotopic to zero, with homotopy given by the system of maps $h'_ n = (-1)^{n + 1}h_ n : E_ n \to E_{n + 1}$. Hence we see that $E$ is acyclic, for example by Homology, Lemma 12.12.5. $\square$

Lemma 14.23.3. Let $\mathcal{A}$ be an abelian category. Let $A$ be an object of $\mathcal{A}$ and let $k$ be an integer. We have $H_ i(s(K(A, k))) = A$ if $i = k$ and $0$ else.

Proof. First, let us prove this if $k = 0$. In this case we have $K(A, 0)_ n = A$ for all $n$. Furthermore, all the maps in this simplicial abelian group are $\text{id}_ A$, in other words $K(A, 0)$ is the constant simplicial object with value $A$. The boundary maps $d_ n = \sum _{i = 0}^ n (-1)^ i \text{id}_ A = 0$ if $n$ odd and $ = \text{id}_ A$ if $n$ is even. Thus $s(K(A, 0))$ looks like this

\[ \ldots \to A \xrightarrow {0} A \xrightarrow {1} A \xrightarrow {0} A \to 0 \]

and the result is clear.

Next, we prove the result for all $k$ by induction. Given the result for $k$ consider the short exact sequence

\[ 0 \to K(A, k) \to E \to K(A, k + 1) \to 0 \]

from Lemma 14.22.4. By Lemma 14.22.1 the associated sequence of chain complexes is exact. By Lemma 14.23.2 we see that $s(E)$ is acyclic. Hence the result for $k + 1$ follows from the long exact sequence of homology, see Homology, Lemma 12.12.6. $\square$

There is a second chain complex we can associate to a simplicial object of $\mathcal{A}$. Recall that by Lemma 14.18.6 any simplicial object $U$ of $\mathcal{A}$ is canonically split with $N(U_ m) = \bigcap _{i = 0}^{m - 1} \mathop{\mathrm{Ker}}(d^ m_ i)$. We define the normalized chain complex $N(U)$ to be the chain complex

\[ \ldots \to N(U_2) \to N(U_1) \to N(U_0) \to 0 \to 0 \to \ldots \]

with boundary map $d_ n : N(U_ n) \to N(U_{n - 1})$ given by the restriction of $(-1)^ nd^ n_ n$ to the direct summand $N(U_ n)$ of $U_ n$. Note that Lemma 14.18.8 implies that $d^ n_ n(N(U_ n)) \subset N(U_{n - 1})$. It is a complex because $d^ n_ n \circ d^{n + 1}_{n + 1} = d^ n_ n \circ d^{n + 1}_ n$ and $d^{n + 1}_ n$ is zero on $N(U_{n + 1})$ by definition. Thus we obtain a second functor

\[ N : \text{Simp}(\mathcal{A}) \longrightarrow \text{Ch}_{\geq 0}(\mathcal{A}). \]

Here is the reason for the sign in the differential.

Lemma 14.23.4. Let $\mathcal{A}$ be an abelian category. Let $U$ be a simplicial object of $\mathcal{A}$. The canonical map $N(U_ n) \to U_ n$ gives rise to a morphism of complexes $N(U) \to s(U)$.

Proof. This is clear because the differential on $s(U)_ n = U_ n$ is $\sum (-1)^ i d^ n_ i$ and the maps $d^ n_ i$, $i < n$ are zero on $N(U_ n)$, whereas the restriction of $(-1)^ nd^ n_ n$ is the boundary map of $N(U)$ by definition. $\square$

Lemma 14.23.5. Let $\mathcal{A}$ be an abelian category. Let $A$ be an object of $\mathcal{A}$ and let $k$ be an integer. We have $N(K(A, k))_ i = A$ if $i = k$ and $0$ else.

Proof. It is clear that $N(K(A, k))_ i = 0$ when $i < k$ because $K(A, k)_ i = 0$ in that case. It is clear that $N(K(A, k))_ k = A$ since $K(A, k)_{k - 1} = 0$ and $K(A, k)_ k = A$. For $i > k$ we have $N(K(A, k))_ i = 0$ by Lemma 14.21.9 and the definition of $K(A, k)$, see Definition 14.22.3. $\square$

Lemma 14.23.6. Let $\mathcal{A}$ be an abelian category. Let $U$ be a simplicial object of $\mathcal{A}$. The canonical morphism of chain complexes $N(U) \to s(U)$ is split. In fact,

\[ s(U) = N(U) \oplus A(U) \]

for some complex $A(U)$. The construction $U \mapsto A(U)$ is functorial.

Proof. Define $A(U)_ n$ to be the image of

\[ \bigoplus \nolimits _{\varphi : [n] \to [m]\text{ surjective}, \ m < n} N(U_ m) \xrightarrow {\bigoplus U(\varphi )} U_ n \]

which is a subobject of $U_ n$ complementary to $N(U_ n)$ according to Lemma 14.18.6 and Definition 14.18.1. We show that $A(U)$ is a subcomplex. Pick a surjective map $\varphi : [n] \to [m]$ with $m < n$ and consider the composition

\[ N(U_ m) \xrightarrow {U(\varphi )} U_ n \xrightarrow {d_ n} U_{n - 1}. \]

This composition is the sum of the maps

\[ N(U_ m) \xrightarrow {U(\varphi \circ \delta ^ n_ i)} U_{n - 1} \]

with sign $(-1)^ i$, $i = 0, \ldots , n$.

First we will prove by ascending induction on $m$, $0 \leq m < n - 1$ that all the maps $U(\varphi \circ \delta ^ n_ i)$ map $N(U_ m)$ into $A(U)_{n - 1}$. (The case $m = n - 1$ is treated below.) Whenever the map $\varphi \circ \delta ^ n_ i : [n - 1] \to [m]$ is surjective then the image of $N(U_ m)$ under $U(\varphi \circ \delta ^ n_ i)$ is contained in $A(U)_{n - 1}$ by definition. If $\varphi \circ \delta ^ n_ i : [n - 1] \to [m]$ is not surjective, set $j = \varphi (i)$ and observe that $i$ is the unique index whose image under $\varphi $ is $j$. We may write $\varphi \circ \delta ^ n_ i = \delta ^ m_ j \circ \psi \circ \delta ^ n_ i$ for some $\psi : [n - 1] \to [m - 1]$. Hence $U(\varphi \circ \delta ^ n_ i) = U(\psi \circ \delta ^ n_ i) \circ d^ m_ j$ which is zero on $N(U_ m)$ unless $j = m$. If $j = m$, then $d^ m_ m(N(U_ m)) \subset N(U_{m - 1})$ and hence $U(\varphi \circ \delta ^ n_ i)(N(U_ m)) \subset U(\psi \circ \delta ^ n_ i)(N(U_{m - 1}))$ and we win by induction hypothesis.

To finish proving that $A(U)$ is a subcomplex we still have to deal with the composition

\[ N(U_ m) \xrightarrow {U(\varphi )} U_ n \xrightarrow {d_ n} U_{n - 1}. \]

in case $m = n - 1$. In this case $\varphi = \sigma ^{n - 1}_ j$ for some $0 \leq j \leq n - 1$ and $U(\varphi ) = s^{n - 1}_ j$. Thus the composition is given by the sum

\[ \sum (-1)^ i d^ n_ i \circ s^{n - 1}_ j \]

Recall from Remark 14.3.3 that $d^ n_ j \circ s^{n - 1}_ j = d^ n_{j + 1} \circ s^{n - 1}_ j = \text{id}$ and these drop out because the corresponding terms have opposite signs. The map $d^ n_ n \circ s^{n - 1}_ j$, if $j < n - 1$, is equal to $s^{n - 2}_ j \circ d^{n - 1}_{n - 1}$. Since $d^{n - 1}_{n - 1}$ maps $N(U_{n - 1})$ into $N(U_{n - 2})$, we see that the image $d^ n_ n ( s^{n - 1}_ j (N(U_{n - 1}))$ is contained in $s^{n - 2}_ j(N(U_{n - 2}))$ which is contained in $A(U_{n - 1})$ by definition. For all other combinations of $(i, j)$ we have either $d^ n_ i \circ s^{n - 1}_ j = s^{n - 2}_{j - 1} \circ d^{n - 1}_ i$ (if $i < j$), or $d^ n_ i \circ s^{n - 1}_ j = s^{n - 2}_ j \circ d^{n - 1}_{i - 1}$ (if $n > i > j + 1$) and in these cases the map is zero because of the definition of $N(U_{n - 1})$. $\square$

Proof. By Lemma 14.23.1 and the functorial decomposition of Lemma 14.23.6. $\square$

Lemma 14.23.8. Let $\mathcal{A}$ be an abelian category. Let $V$ be a simplicial object of $\mathcal{A}$. The canonical morphism of chain complexes $N(V) \to s(V)$ is a quasi-isomorphism. In other words, the complex $A(V)$ of Lemma 14.23.6 is acyclic.

Proof. Note that the result holds for $K(A, k)$ for any object $A$ and any $k \geq 0$, by Lemmas 14.23.3 and 14.23.5. Consider the hypothesis $IH_{n, m}$: for all $V$ such that $V_ j = 0$ for $j \leq m$ and all $i \leq n$ the map $N(V) \to s(V)$ induces an isomorphism $H_ i(N(V)) \to H_ i(s(V))$.

To start of the induction, note that $IH_{n, n}$ is trivially true, because in that case $N(V)_ n = 0$ and $s(V)_ n = 0$.

Assume $IH_{n, m}$, with $m \leq n$. Pick a simplicial object $V$ such that $V_ j = 0$ for $j < m$. By Lemma 14.22.2 and Definition 14.22.3 we have $K(V_ m, m) = i_{m!} \text{sk}_ mV$. By Lemma 14.21.10 the natural morphism

\[ K(V_ m, m) = i_{m!} \text{sk}_ mV \to V \]

is injective. Thus we get a short exact sequence

\[ 0 \to K(V_ m, m) \to V \to W \to 0 \]

for some $W$ with $W_ i = 0$ for $i = 0, \ldots , m$. This short exact sequence induces a morphism of short exact sequence of associated complexes

\[ \xymatrix{ 0 \ar[r] & N(K(V_ m, m)) \ar[r] \ar[d] & N(V) \ar[r] \ar[d] & N(W) \ar[r] \ar[d] & 0 \\ 0 \ar[r] & s(K(V_ m, m)) \ar[r] & s(V) \ar[r] & s(W) \ar[r] & 0 } \]

see Lemmas 14.23.1 and 14.23.7. Hence we deduce the result for $V$ from the result on the ends. $\square$


Comments (0)


Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.




In order to prevent bots from posting comments, we would like you to prove that you are human. You can do this by filling in the name of the current tag in the following input field. As a reminder, this is tag 0194. Beware of the difference between the letter 'O' and the digit '0'.